Generation of a Digital Elevation Model as a subsidy in urban planning in Manaus/AM – Brazil (Research, Society and Development, 2022)
Most Brazilian cities, the Regional Municipal Master Plans, end up pushing away environmental issues from urban management. In this sense, the purpose of this study was to generate a Digital Elevation Model, using SRTM images - (Shuttle Radar Topography Mission) Radar in the city of Manaus, to support the land use policy. The methodology followed four stages: the first was performed a study of theoretical and cartographic reference of the study area; in a second moment was acquired the data and were subsequently processed for possible interpretations; in the third step was the extraction of contour lines from the acquired images; and, the fourth stage took place analysis and discussion of results. The urban area of ​​Manaus according to pre-established ratings have a major soft, wavy form that showed variations 3-8% slope and some higher areas reaching about 117 meters, forms the slopes enable the superficial processes and shape relief dissected the urban site of Manaus. The study enabled the knowledge and insight of the topography of the region that is marked by various social problems that order and segregates the space of the city, this knowledge directly influence the strategic urban planning of the city.